Inventing the Third World In Search of Freedom for the Postwar Global South - Prakash, Gyan; Adelman, Jeremy (Histories of Internationalism, 2022)
An edited collection that explores the ways in which the global south reimagined the future world order at the end of the Second World War, and the cultural and intellectual breakthroughs that these new narratives created.